2013
DOI: 10.1186/1472-6963-13-443
|View full text |Cite
|
Sign up to set email alerts
|

Quality of antenatal care services at public health facilities of Bahir-Dar special zone, Northwest Ethiopia

Abstract: BackgroundAntenatal care (ANC) is one of the evidence based interventions to decrease the probability of bad health outcomes for mothers and their newborns. Effectiveness of antenatal care, however, relies on the quality of care provided during each antenatal care visit. Hence this study attempted to assess the quality of antenatal care services at public health facilities of Bahir-Dar special zone, North Western Ethiopia.MethodsA facility based cross-sectional study employing both quantitative and qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
9
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 3 publications
12
81
9
17
Order By: Relevance
“…This study revealed that 57% of the pregnant women initiated ANC visit within the first trimester of gestation. This finding is higher than what was found in other studies in sub-Saharan Africa [27][28][29][30] but lower than what is recommended by WHO [3,31]. This divergence could be due to the economic, socio-cultural and timing differences between the studies and among the study population as suggested in other studies [32,33].…”
Section: Discussioncontrasting
confidence: 70%
“…This study revealed that 57% of the pregnant women initiated ANC visit within the first trimester of gestation. This finding is higher than what was found in other studies in sub-Saharan Africa [27][28][29][30] but lower than what is recommended by WHO [3,31]. This divergence could be due to the economic, socio-cultural and timing differences between the studies and among the study population as suggested in other studies [32,33].…”
Section: Discussioncontrasting
confidence: 70%
“…Some studies have pointed to quality deficits in the delivery of basic maternal and child-health services. [11][12][13][14] However, unlike for coverage, there is no systematic examination of health-care quality that would permit benchmarking and tracking of progress over time. This is increasingly important as there is renewed interest in strengthening the role of integrated primary care in countries where investments have predominantly targeted communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…). They are commonly used to assess patients’ satisfaction with the health care services received (Ejigu, Woldie, and Kifle ; Alonge et al. ; Asfaw et al.…”
Section: Summary Of Sampling Methods For Patient Exit Interviewsmentioning
confidence: 99%